2016
DOI: 10.1371/journal.pone.0167518
|View full text |Cite|
|
Sign up to set email alerts
|

A Single Pair of Serotonergic Neurons Counteracts Serotonergic Inhibition of Ethanol Attraction in Drosophila

Abstract: Attraction to ethanol is common in both flies and humans, but the neuromodulatory mechanisms underlying this innate attraction are not well understood. Here, we dissect the function of the key regulator of serotonin signaling—the serotonin transporter–in innate olfactory attraction to ethanol in Drosophila melanogaster. We generated a mutated version of the serotonin transporter that prolongs serotonin signaling in the synaptic cleft and is targeted via the Gal4 system to different sets of serotonergic neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…Neuromodulation provides a means of functional reconfiguration of circuit activity in a fixed wiring diagram. Bidirectional modulation of behavioral output by serotonin has also been described in adult Drosophila behaviors (Xu et al, 2016).…”
Section: Innate Olfactory Preferences Depend On Feeding Statementioning
confidence: 94%
“…Neuromodulation provides a means of functional reconfiguration of circuit activity in a fixed wiring diagram. Bidirectional modulation of behavioral output by serotonin has also been described in adult Drosophila behaviors (Xu et al, 2016).…”
Section: Innate Olfactory Preferences Depend On Feeding Statementioning
confidence: 94%
“…Specifically, we found that PN axons directly excite CSDn terminals in the LH in an odor specific manner while CSDn branches in the AL are inhibited. Previous studies have shown that the CSDn soma is also inhibited by odors and that stimulation of the CSDn has little impact on olfactory circuitry in the AL (30), despite the CSDn being critical for normal olfactory behavior (27,28). Our current study resolves this issue by suggesting instead that the CSDn modulates behavior by affecting odorprocessing in the LH (Fig.…”
Section: Multi-dendritic Processingmentioning
confidence: 50%
“…CSDns can be targeted genetically (26) and are critical for various olfactory behaviors involving appetitive (27) and pheromonal odorants, including cis-vaccenyl acetate (cVA) (28). The modulation of cVA-evoked behavioral responses is especially interesting because the CSDns are thought to participate in top-down modulation and to have their effects mainly in the first olfactory relay, the antennal lobe (AL) (24,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin immunolabeling was observed in processes within all optic ganglia as well as 93 a cluster of 8-10 cell bodies in the accessory medulla ( Figure 1D, G). The cell bodies 94 correspond to cluster LP2 (or Cb1), previously shown to project into the medulla (Nässel, 1988;95 Valles et al, 1988;Xu et al, 2016). Many of the neuronal processes expressing serotonin receptor MiMIC-GAL4 driven GFP showed close apposition to serotonergic boutons ( Figure 1D…”
Section: Serotoninergic Circuitry In the Optic Lobe 73mentioning
confidence: 84%